Study of the genus Meleonoma Meyrick, 1914 (Lepidoptera: Autostichidae) from China, with descriptions of fifteen new species - Wang, Shuxia; Zhu, Xiaoju (Zootaxa, 2020)
Fifteen new species of the genus Meleonoma Meyrick are described: M. anisodonta sp. nov., M. catenata sp. nov., M. dilativalva sp. nov., M. dorsibacilliformis sp. nov., M. lanceolata sp. nov., M. longaedeaga sp. nov., M. longiprocessa sp. nov., M. lunulata sp. nov., M. papillata sp. nov., M. parvissima sp. nov., M. rugulosa sp. nov., M. tenuiuncata sp. nov., M. tianmushana sp. nov., M. triacantha sp. nov. and M. ventrospinosa sp. nov.; one species, M. aridula (Meyrick, 1910), is newly recorded from China; and the female of M. microbyrsa (Wang, 2003) is described for the first time. Images of both adults and genitalia are provided. All species are divided into two species-groups, and a key to each group as well as a map showing the distribution of each group in China are given.